2008
DOI: 10.1084/jem.20072182
|View full text |Cite
|
Sign up to set email alerts
|

Somatically acquired JAK1 mutations in adult acute lymphoblastic leukemia

Abstract: Aberrant signal transduction contributes substantially to leukemogenesis. The Janus kinase 1 (JAK1) gene encodes a cytoplasmic tyrosine kinase that noncovalently associates with a variety of cytokine receptors and plays a nonredundant role in lymphoid cell precursor proliferation, survival, and differentiation. We report that somatic mutations in JAK1 occur in individuals with acute lymphoblastic leukemia (ALL). JAK1 mutations were more prevalent among adult subjects with the T cell precursor ALL, where they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
274
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(290 citation statements)
references
References 29 publications
15
274
1
Order By: Relevance
“…46,47 A recent report identified a JAK3 A572V mutation in 1 of 30 MF patients 48 studied. We have found no evidence for the most common activating mutations, JAK1 V658F and JAK2 V617, in primary SS samples.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 A recent report identified a JAK3 A572V mutation in 1 of 30 MF patients 48 studied. We have found no evidence for the most common activating mutations, JAK1 V658F and JAK2 V617, in primary SS samples.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these observations suggested that the poor-outcome, IKZF1-deleted, BCR-ABL1-negative cases might harbor activating tyrosine kinase mutations. The JAK-STAT pathway may mediate BCR-ABL1 signaling and transformation (7,8), and JAK1 and JAK2 are mutated in myeloproliferative diseases (9), Down syndrome-associated ALL (DS-ALL), and T lineage ALL (10)(11)(12). Here, we have performed genomic resequencing of JAK1, JAK2, JAK3, and TYK2 in 187 diagnostic samples from this high risk B-progenitor ALL cohort that had available DNA and gene expression profiling data.…”
Section: Ikaros ͉ Kinase ͉ Mutationmentioning
confidence: 99%
“…JAK1 pseudokinase mutations have also been described in T-lineage ALL, albeit more commonly in adults than in children. 61,65 The frequency of JAK2 mutations in large cohorts of adult ALL cases has not been determined. Similar to the JAK2 V617F mutation, the JAK1 and JAK2 mutations observed in ALL are transforming in vitro, conferring cytokine-independent growth and constitutive Jak-Stat activation when introduced into Ba/F3 cells (a murine pro-B-cell line) expressing the erythropoietin or thrombopoietin receptors.…”
Section: Genetic Characterization Of Bcr-abl1-like Phà Allmentioning
confidence: 99%